Laparoscopic resolution of a case of "Candy Cane" in a postoperative period of Gastric Bypass - Varela Vega, Martín; Beraldo, Gerardo; Santiago, Pablo; Baranov, Sofía; Da Rosa, Agustina (Cirugía del Uruguay, 2021)
Gastric bypass (BPG) is a bariatric surgery technique with proven efficacy in the control of obesity and the resolution of associated diseases, such as diabetes and hypertension. Postoperative abdominal pain away from LGA is a real challenge, and requires an understanding of the surgical technique and the possible causes that originate the pain for its etiological diagnosis. The main causes of pain are neobocal ulcer, internal hernias (due to Petersen's space or mesenteric gap), symptomatic gallstones, and “candy cane” syndrome (or “Candy Cane syndrome” by its Anglo-Saxon name). ). It results from an excessive length of the blind jejunal stump of the alimentary loop, after the gastrojejunal anastomosis. When it measures more than 4 cm it can fill with food, acting as a bag or reservoir, causing pain, nausea or vomiting. The diagnosis arises from the clinic and a contrasted study that demonstrates the excessive length of the end of the alimentary loop. Treatment is surgical and the disappearance of symptoms confirms the diagnosis. Watch the video at: https://www.youtube.com/watch?v=wxLU_Xh8o7Q